Managing Reputation Risk in Supply Chains: The Role of Risk Sharing Under Limited Liability - Dhingra, Vibhuti; Krishnan, Harish (Management Science, 2021)
When a supplier fails to comply with social and environmental standards, the buyer’s reputation suffers. Reputation costs can typically be very high for the buyer, whereas the supplier’s liability is often limited. Conventional procurement strategies such as dual sourcing mitigate the buyer’s operational risk, but they often do so at the expense of increasing its reputation risk and sourcing costs. In this paper, we propose a risk-sharing contract for managing the buyer’s reputation concerns. We find that by sharing some of the supplier’s operational loss, the buyer may (in some conditions) decrease its reputational risk, but this has to be balanced against an increase in the operational risk. Risk sharing also reduces sourcing costs because the buyer takes on some of the worst-case loss of a wealth-constrained supplier. These results suggest that risk sharing can be superior, as a procurement strategy, to conventional approaches such as dual sourcing or penalty contracts. This is true when reputation and sourcing costs are a significant concern and operational costs are not that high. Under some conditions, the buyer may choose risk sharing even if it increases reputation risk in order to reduce procurement costs. This paper was accepted by Victor Martínez-de-Albéniz, operations management.